Comparison of Mechanical Outputs Between the Traditional and Ballistic Bench Press: Role of the Type of Variable. Issue 8 (August 2020) - Pestaña-Melero, Francisco L.; Jaric, Slobodan; Pérez-Castilla, Alejandro; Rojas, Francisco J.; García-Ramos, Amador
Abstract : Abstract: Pestaña-Melero, FL, Jaric, S, Pérez-Castilla, A, Rojas, FJ, and García-Ramos A. Comparison of mechanical outputs between the traditional and ballistic bench press: role of the type of variable. J Strength Cond Res 34(8): 2227–2234, 2020—This study aimed to comprehensively explore the differences in mechanical outputs between the bench press (BP) and the bench press throw (BPT) exercises performed by 21 men (age: 22.0 ± 4.2 years, body mass: 73.4 ± 7.7 kg, height: 177.2 ± 8.0 cm, and concentric-only [C-O] BP 1 repetition maximum: 81.3 ± 6.8 kg) against a fixed external load of 27 kg using both the (C-O) and eccentric-concentric (E-C) execution techniques. The types of variables collected by means of a linear velocity transducer were the traditional mean values (i.e., from the first positive velocity until the barbell reaches maximum height), mean propulsive values (i.e., from the first positive velocity until the barbell acceleration become lower than gravity), mean values of the acceleration phase (i.e., from the first positive velocity until the barbell acceleration become negative), and maximum values (i.e., the highest instantaneous value of the concentric phase) of force, velocity, and power. The magnitude of the effect sizes (the negative sign indicates a higher value for the BP as compared to the BPT) ranged from −0.10 to −2.19 for force, 0.28 to 1.30 for velocity, and −0.73 to 0.67 for power variables, remaining mainly similar for the (C-O) and (E-C) execution techniques. These results highlight that the comparison of force, velocity, and power outputs between the BP and BPT exercises is largely affected by the type of variable considered. The shortcomings of linear position transducers in accurately determining the end point of the concentric phase suggest that the maximum values, particularly the maximum velocity, should be reported to assess ballistic performance.